Correlation of Hypocalcemia with eGFR in Chronic Kidney Disease: A Cross Sectional Study in Marine City Medical College and Hospital - Hussain, Farhad; Kumar Dutta, Pradip (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2025)
Background: Chronic Kidney Disease (CKD) poses a significant global health challenge. Its ramifications include advancing to End-Stage Renal Disease (ESRD) developing various complications stemming from compromised kidney function, and heightened vulnerability to Cardiovascular Disease (CVD). Interestingly, even within the bounds of normalcy, lower serum Calcium (Ca) levels emerge as a risk factor for precipitating a swift decline in estimated Glomerular Filtration Rate (eGFR) in CKD. Through extensive multivariable correlation analyses, it's been unveiled that serum calcium levels exhibit a correlation with eGFR. The current study aims at elucidating a link between serum calcium levels and eGFR among CKD patients. Materials and methods: A cross-sectional study was conducted from January 2023 to December 2023, by the Department of Biochemistry in conjunction with the Department of Nephrology at Marine City Medical College & Hospital (MCMCH). Purposive sampling was employed to recruit a total of 224 subjects of 18 years and above, after following the inclusion criteria and obtaining permission from ethical/institutional review board (IRB). The study population was grouped as CKD: stage III (eGFR 30-59 ml/min/1.73m²) stage IV (eGFR 15-29 ml/min/1.73m²) and stage V (eGFR<15ml/min/1.73m²). A comprehensive clinical profile was documented for each participant, encompassing key variables such as serum creatinine, serum calcium and eGFR. Results: The study revealed Male predominance (54%) with mean age 56.22±12.78. Among the study population 173 (77.2%) subjects had low serum calcium level (<8.5 mg/dl) of which 127 subjects were in CKD stage V. ANOVA test was significant for serum creatinine, serum calcium and eGFR in different stages of CKD. Pearson’s correlation showed positive correlation between the eGFR and low serum calcium with a significant association of CKD stages (stage III, IV, V) with decreased serum calcium level in the study cases [c2 = 14.90; p= 0.0005]. Conclusion: The study revealed a significant association between Hypocalcemia and decreased eGFR in CKD. Chatt Maa Shi Hosp Med Coll J; Vol.23 (2); July 2024; Page 96-100